Sustainable Management: An Institutional Inquiry for Common-Pool Resources (Case Study of Cirata Reservoir, West Java) - KUSUMAWARDHANI, ANDINI (Kirana Publisher (KNPub), 2025)
(Cirata Reservoir area is one of the public water resources resulting from the damming of the Citarum River, which has the main function as a hydroelectric power plant (PLTA). The reservoir is also becoming a centre of economic activity for the surrounding community, which is for the floating net cage business and the distribution of floating cage products. The high level of economic activity that occurs in Cirata Reservoir has the consequence of causing various problems that threaten the sustainability of Cirata Reservoir. The conditions that occur in Cirata Reservoir indicate that there is institutional ineffectiveness in the management of reservoir resources. If this institutional ineffectiveness continues, it will threaten the existence of Cirata Reservoir, whose function is needed by many parties. This study aims to analyze the existing institutions in the management of Cirata Reservoir in West Java through in-depth interviews with resource persons and content analysis of existing regulations. The results show that regulations related to the management and utilization of Cirata Reservoir already exist, but their implementation is still not optimal. Institutions have been established based on existing regulations with the roles of each stakeholder and the relationships between them but have not been implemented effectively. Coordination, supervision, and law enforcement are important keys in implementing the institutional design of Cirata Reservoir management to realize sustainable reservoir management.